Invastor logo
No products in cart
No products in cart

Ai Content Generator

Ai Picture

Tell Your Story

My profile picture
66be6dc10ed85dd44e3cf630

Find the derivative of the function: 𝑓 ( π‘₯ ) = 𝑒 π‘₯ 2 β‹… sin ⁑ ( π‘₯ ) f(x)=e x 2 β‹…sin(x)

6 months ago
61

To find the derivative of the given function, 𝑓(π‘₯) = 𝑒^π‘₯^2 β‹… sin(π‘₯), we can use the product rule. The product rule states that if we have two functions, 𝑒(π‘₯) and 𝑣(π‘₯), then the derivative of their product is given by:


𝑑(𝑒(π‘₯)⋅𝑣(π‘₯))/𝑑π‘₯ = 𝑒(π‘₯)⋅𝑑𝑣(π‘₯)/𝑑π‘₯ + 𝑣(π‘₯)⋅𝑑𝑒(π‘₯)/𝑑π‘₯.


In our case, 𝑒(π‘₯) = 𝑒^π‘₯^2 and 𝑣(π‘₯) = sin(π‘₯). Let's find the derivatives of these two functions first.


The derivative of 𝑒(π‘₯) = 𝑒^π‘₯^2 can be found using the chain rule. The chain rule states that if we have a function 𝑔(π‘₯) = 𝑓(𝑒(π‘₯)), then the derivative of 𝑔(π‘₯) with respect to π‘₯ is given by:


𝑑𝑔(π‘₯)/𝑑π‘₯ = 𝑑𝑓(𝑒(π‘₯))/𝑑𝑒(π‘₯) β‹… 𝑑𝑒(π‘₯)/𝑑π‘₯.


In our case, 𝑔(π‘₯) = 𝑒^π‘₯^2 and 𝑓(𝑒) = 𝑒^𝑒. So, applying the chain rule, we have:


𝑑𝑔(π‘₯)/𝑑π‘₯ = 𝑑𝑓(𝑒)/𝑑𝑒 β‹… 𝑑𝑒(π‘₯)/𝑑π‘₯ = 𝑒^𝑒 β‹… 2π‘₯.


Since 𝑒 = π‘₯^2, we can substitute 𝑒 in terms of π‘₯:


𝑑𝑔(π‘₯)/𝑑π‘₯ = 𝑒^(π‘₯^2) β‹… 2π‘₯.


Next, let's find the derivative of 𝑣(π‘₯) = sin(π‘₯). The derivative of sin(π‘₯) is cos(π‘₯). Therefore:


𝑑𝑣(π‘₯)/𝑑π‘₯ = cos(π‘₯).


Now, let's apply the product rule to find the derivative of 𝑓(π‘₯) = 𝑒^π‘₯^2 β‹… sin(π‘₯):


𝑑(𝑓(π‘₯))/𝑑π‘₯ = 𝑒(π‘₯)⋅𝑑𝑣(π‘₯)/𝑑π‘₯ + 𝑣(π‘₯)⋅𝑑𝑒(π‘₯)/𝑑π‘₯ = 𝑒^(π‘₯^2)β‹…cos(π‘₯) + sin(π‘₯)β‹…2π‘₯.


Therefore, the derivative of 𝑓(π‘₯) = 𝑒^π‘₯^2 β‹… sin(π‘₯) is 𝑒^(π‘₯^2)β‹…cos(π‘₯) + sin(π‘₯)β‹…2π‘₯.


I hope this explanation helps! Let me know if you have any further questions.


References:

- Khan Academy. (n.d.). Product rule. Retrieved from https://www.khanacademy.org/math/ap-calculus-ab/ab-differentiation-1-new/ab-2-1/v/product-rule

User Comments

Related Posts

    There are no more blogs to show

    Β© 2025 Invastor. All Rights Reserved